2018
DOI: 10.15287/afr.2018.1187
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of the oak lace bug Corythucha arcuata (Say.) in Romania: a first extended reporting

Abstract: Invasion of the oak lace bug Corythucha arcuata (Say.) in Romania: a first extended reporting. Ann. For. Res. 61(2): 161-170.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 7 publications
4
26
0
1
Order By: Relevance
“…Of all the invasive insect species on woody plants found in the current study, none are new to Romania, all have been reported before in the country through other studies (Olenici and Duduman, 2016;Olenici et al, 2018;Nețoiu et al, 2018;Tomescu et al, 2018). However, in Bucharest green areas only four species out of the 12 have been reported previously: Cameraria ohridella, Corythucha arcuata, Corythucha ciliata and Cydalima perspecalis (Ciceoi et al, 2017;Tomescu et al, 2018), the rest the species being reported for the first time in Bucharest: Aproceros leucopoda, Dasineura gleditchiae, Eopineus strobus, Macrosaccus robiniella, Nematus tibialis, Obolodiplosis robiniae, Parectopa robiniella, Prociphilus fraxinifoli.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Of all the invasive insect species on woody plants found in the current study, none are new to Romania, all have been reported before in the country through other studies (Olenici and Duduman, 2016;Olenici et al, 2018;Nețoiu et al, 2018;Tomescu et al, 2018). However, in Bucharest green areas only four species out of the 12 have been reported previously: Cameraria ohridella, Corythucha arcuata, Corythucha ciliata and Cydalima perspecalis (Ciceoi et al, 2017;Tomescu et al, 2018), the rest the species being reported for the first time in Bucharest: Aproceros leucopoda, Dasineura gleditchiae, Eopineus strobus, Macrosaccus robiniella, Nematus tibialis, Obolodiplosis robiniae, Parectopa robiniella, Prociphilus fraxinifoli.…”
Section: Discussionsupporting
confidence: 55%
“…In Romania, the studies that addressed invasive forest insect species considered the host trees found in different types of ecosystems: forests, plantations, street tree alignments, isolated trees but also parks and urban areas (Ciceoi et al, 2017;Nețoiu et al, 2018;Olenici et al, 2018;Tomescu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In Switzerland, which borders Italy, it appeared in 2002, in nearby France only in 2017, and in Austria only in 2019 (Zielińska & Lis, 2020). In Hungary, Croatia, and Serbia, the bug was found in 2013 (Csóka et al, 2020), in Romania in 2015 (Tomescu et al, 2018), in Slovakia in 2018 (Zúbrik et al, 2019), and in the Czech Republic in 2019 (Nikolić et al, 2019). The last country seems to be the most northern territory of OLB penetration in Central Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Например, Quercus rubra во многих работах приведён в качестве кормовой породы клопа как в пределах естественного, так и вторичного ареалов [36]. В то же время рядом исследователей отмечена непоражаемость этого вида дубовой кружевницей [2,42].…”
Section: рис 1 распределение дубовых лесов в крыму [9 с изменениями]unclassified